A New Improvement of Reverse Voltage Single Phase Multilevel Inverter Topology - Lada, Musa Yusup; Khamis, Aziah; Azri, Maaspaliza; Zolkifri, Nur Izzati; Md Nawawi, Mohamad Riduwan; Gan, Chin Kim (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The widely use of a multilevel inverter (MLI) in high power system applications proves that MLI is highly superior to the conventional inverter in reducing harmonic distortion. Basically there are three topologies of multilevel inverters that commonly used, which is cascaded H-Bridge, diode clamped and flying capacitor. Even though these inverters can produce low harmonic distortion, many switching devices are needed to perform high voltage level. However, the usage of a numerous number of switching devices can produce high switching losses. It also increases weight, space, cost and switching complexity of the hardware. Therefore, this study attempts to develop low harmonic distortion with less switching devices by improving the reverse voltage topology using MATLAB/Simulink software. The performance of proposed scheme was evaluated through an extensive test considering several scenarios such as amplitude modulation ratio (Ma), total harmonic distortion (THD) and switching scheme under various operating points. Moreover the effectiveness of the proposed scheme was verified by comparing its result with conventional MLI such as reverse voltage MLI topology and cascaded H-bridge topology.